Smart sensors for estimation of power interaction of an athlete with water surface when paddling in the cycle of rowing locomotions - Lukashevich, D.; Huseynov, D.; Minchenya, A.; Bubulis, A.; Vežys, J. (Journal of Complexity in Health Sciences, 2020)
Theoretical justification for the choice of the strain-resistant element location on the loom of the canoe paddle in order to register the power parameters of interaction of an athlete with the paddle in natural conditions of rowing locomotions is presented in the article. Taking into account the introduced simplifications, a classical task of calculating the materials resistance from which the loom of the paddle is manufactured is submitted. The obtained result is reliable and allows with sufficient degree of accuracy to determine mechanical stresses arising in the process of rowing in location of measuring devices - tensometers, which provides registration of objective indices characterizing power of forces applied by an athlete in the support (water) part of a stroke. Besides, based on the MEMS-sensors readings, mathematical calculation of forces applied to the paddle in the process of rowing was made, which in specified conditions allows to estimate regularities of values ratio of the recorded dynamic parameters.